Jorden kalder på Dansk Plakatmuseum - Poliakova, Ekatarina (Den Gamle By: Danmarks Købstadmuseum (Årbog), 2024)
Forurening, miljø og klima har været på dagsordenen længe. Endda før plakater for alvor blev masseudbredt og brugt til at sprede budskabet om, at vi skal passe på jorden. Den Gamle By udvalgte 170 plakater fra det seneste århundrede til udstillingen, der åbnede i februar 2023. Akademisk medarbejder Ekaterina Poliakova fortæller historien. The Environmental History of Posters Pollution, environment and climate have been on the agenda for a while. Even before posters became properly widespread and used to convey the message that we should take care of the earth. Den Gamle By selected 170 posters from the last century to show how we have discussed the topic historically. Each poster is a unique instance of history. But when viewed side by side you can discover interesting narratives, parallels and references. The dates of the environmental and climate-related posters highlight how we moved from talking about nature, environment and pollution to talking about climate after the 1990s.